Do tobacco and cannabis use and co-use predict lung function: A longitudinal study. (March 2023) - Najman, Jake M.; Bell, Scott; Williams, Gail M.; Clavarino, Alexandra M.; Scott, James G.; McGee, Tara R.; Mamun, Abdullah A.
Abstract: Background: Use of tobacco and cannabis is common and has been reported to predict lung function. Less is known about co-use of tobacco and cannabis and their impact on changes in lung function to early adulthood. Research question: The study examines whether cigarette smoking or cannabis use and co-use are each associated with lung function in a population sample of young adults. Study design and methods: Data are from a prospective cohort study of cigarette smoking, cannabis use and co-use at 21 and 30 years of age and lung function (FVC, FEV1, FEV1 /FVC) measured at 30 years. Lung function results are transformed using Global Lung Function Formulae. Subjects are the children of pregnant women who were recruited into the cohort study over the period 1981–3. Respondents were administered a spirometry assessment at 21 and 30 years of age. These respondents completed a smoking and cannabis use questionnaire at 21- and 30-year follow-ups. Results: Cigarette smoking (with or without cannabis use) is associated with reduced airflow. There is no consistent association between cannabis use and measures of lung function. The co-use of tobacco and cannabis appears to entail no additional risk to lung function beyond the risks associated with tobacco use alone. Interpretation: Persistent cigarette smoking is associated with reduced airflow even in young adults. Cannabis use does not appear to be related to lung function even after years of use. Highlights: Cigarette smoking and cannabis use and co-use are risk factors for impaired lung function. By 30 years, those who have smoked cigarettes since adolescence already show evidence of impairment of lung function. By 30 years, those who used cannabis since the adolescent period do not appear to have evidence of impaired lung function. Co-use of tobacco and cannabis does not appear to predict lung function beyond the effects of tobacco use alone.